2010
DOI: 10.1007/s12011-010-8671-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of FeCl3 and Fe–EDTA on the Development of Psoriasis

Abstract: The effects of FeCl₃ and Fe-EDTA on the development of psoriasis were studied in the mouse model of vaginal epithelium and tail epidermis. The mitoses of vaginal epithelial cell in female mice of their estrogenic stage and the formation of granular cell layers in male mouse tail scale were observed. Mice were randomly divided into eight groups and treated with normal saline, methotrexate, and different doses of two iron forms, FeCl₃ and Fe-EDTA, respectively, for 10 days. To explore the influence of FeCl₃ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Its clinical use for the treatment of psoriasis has greatly inereased since it was approved by the US FDA in the previous century [25]. However, because of its effectiveness we have successfully used MTX as the positive control in the animal model in our previous and present antipsoriasis experiments [28,29]. However, because of its effectiveness we have successfully used MTX as the positive control in the animal model in our previous and present antipsoriasis experiments [28,29].…”
Section: Discussionmentioning
confidence: 97%
“…Its clinical use for the treatment of psoriasis has greatly inereased since it was approved by the US FDA in the previous century [25]. However, because of its effectiveness we have successfully used MTX as the positive control in the animal model in our previous and present antipsoriasis experiments [28,29]. However, because of its effectiveness we have successfully used MTX as the positive control in the animal model in our previous and present antipsoriasis experiments [28,29].…”
Section: Discussionmentioning
confidence: 97%
“…Some Authors claim that iron may be found in excess in serum ofpsoriatic patients , whereas some other Authors have observed significantly low serum iron levels in psoriatic patients . On psoriatic experimental models, very recently a possible therapeut ic effect of iron has been demonstrated by inhibition of the mitoses of mice vaginal epithelial cells, and promotion of granular layer formation in mice tail scales (13).…”
Section: Discussionmentioning
confidence: 99%